Democracy Crisis and the Rise of Datacracy - Putro, Widodo Dwi (Faculty of Law, Universitas Padjadjaran, 2024)
There is no permanent constitutional and political-legal system. Scientists also predict that the phenomenon of the rise of datacracy with big data and algorithms will replace the democratic system. In this research, the author aims to answer the following questions: (i) Why is democracy bound to be replaced by datacracy? (ii) what alternative options can be proposed to bridge the legal and political implications that might occur if datacracy replaces democracy? The author uses literature studies and an interdisciplinary approach to critique and offer ideas in this study. It is proposed, among other things, that datacracy will not eliminate people's sovereignty; instead, it will only narrow down democratic instruments such as people's representatives and political parties because they will no longer be needed. Such representative democracy is likely to become obsolete because the people will be able to actively participate in conveying their aspirations directly, without going through the people's representative system, by inputting their needs, interests, and various problems through the datacracy platform.DOI: https://doi.org/10.22304/pjih.v11n1.a3